2007
DOI: 10.3102/0013189x07308739
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Quality, Opportunity Gap, and National Achievement in 46 Countries

Abstract: The 2003 Trends in International Mathematics and Science Study data from 46 countries showed that, although the national level of teacher quality in the United States was similar to the international average, the opportunity gap in students' access to qualified teachers between students of high and low socioeconomic status (SES) was among the largest in the world. Cross-national analyses revealed that the countries with better teacher quality produced higher mathematics achievement.However, larger opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
242
2
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(272 citation statements)
references
References 59 publications
5
242
2
14
Order By: Relevance
“…As noted by the NA (2007), teacher quality is widely recognized by the policymakers, practitioners and researchers alike to be the most powerful influence on a student's academic performance. A cross-sectional analysis of the 2003 Trends in International Mathematics and Science Study data across 46 countries showed that countries with better quality teachers produced higher mathematics achievement compared to those with poor quality teachers (Akiba et al, 2007). Numerous studies on teacher quality (Darling-Hammond and Youngs, 2002;Rice, 2003;Wayne and Youngs, 2003) have been reported and most of these studies focused on teacher certification, subject-matter knowledge, pedagogical knowledge and teaching experience, since these qualities of teachers are associated with high student achievement.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by the NA (2007), teacher quality is widely recognized by the policymakers, practitioners and researchers alike to be the most powerful influence on a student's academic performance. A cross-sectional analysis of the 2003 Trends in International Mathematics and Science Study data across 46 countries showed that countries with better quality teachers produced higher mathematics achievement compared to those with poor quality teachers (Akiba et al, 2007). Numerous studies on teacher quality (Darling-Hammond and Youngs, 2002;Rice, 2003;Wayne and Youngs, 2003) have been reported and most of these studies focused on teacher certification, subject-matter knowledge, pedagogical knowledge and teaching experience, since these qualities of teachers are associated with high student achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Using student-level data, Montt (2011) suggests that a more equitable distribution of high-quality teachers reduces dispersion in achievement. In related work, Akiba et al (2007), employing nationally aggregated data, found that although high-quality teachers improve mean performance, their equitable distribution does not reduce the gap between high-and low-SES students. It is unclear whether these distinct results are due to the differing levels of aggregation or to substantive differences in the effect of teacher quality on SES gaps, as opposed to score dispersion more generally.…”
Section: Efforts To Mitigate Educational Inequalitymentioning
confidence: 99%
“…Previous research has reported that school resources and learning environments are strongly associated with educational outcomes (Chiu and Khoo, 2005). Of all school resources, most researchers agree that qualified teachers are the most important for student learning (Akiba, LeTendre & Scribner, 2007;Darling-Hammond & Ball, 1997;Darling-Hammond, Holtzman, Gatlin & Vasquez Heilig, 2005;Hanushek, 2007;Hattie, 2009). …”
Section: Introductionmentioning
confidence: 99%